Cerebral-Cardiac Syndrome and Diabetes: Cardiac Damage After Ischemic Stroke in Diabetic State - Lin, Hong-Bin; Li, Feng-Xian; Zhang, Jin-Yu; You, Zhi-Jian; Xu, Shi-Yuan; Liang, Wen-Bin; Zhang, Hong-Fei (Frontiers in Immunology, 2021)
Cerebral-cardiac syndrome (CCS) refers to cardiac dysfunction following varying brain injury. Ischemic stroke is strongly evidenced to induce CCS characterizing as arrhythmia, myocardial damage and heart failure. CCS attributes to the second leading cause of death expect of neurological-related death in post-stroke stage, however the responsible mechanisms are obscure. Studies indicated the possible mechanisms including insular cortex injury, autonomic imbalance, catecholamine surge, immune response and systemic inflammation. Of note, the characteristics of the stroke population reveal a common comorbidity with diabetes. The close and causative correlation of diabetes and stroke directs the involvement of diabetes in CCS. Nevertheless, the role of diabetes and its corresponding molecular mechanisms in CCS have not been clarified. Here we conclude the features of CCS and the potential role of diabetes in CCS. Diabetes drives establish a “primed” inflammatory microenvironment and further induces severe systemic inflammation after stroke. The boosted inflammation is suspect to provoke cardiac pathological changes, hence exacerbate CCS. Importantly, as the key element of inflammation, NOD-like receptor pyrin domain containing 3 (NLRP3) inflammasome is indicated to play an important role in diabetes and stroke, and the sequential CCS. Overall, we characterize the corresponding role of diabetes in CCS and speculate a link of NLRP3 inflammasome between them.